2019
DOI: 10.1371/journal.pone.0225708
|View full text |Cite
|
Sign up to set email alerts
|

Using morphological attributes for the fast assessment of nutritional responses of Buddhist pine (Podocarpus macrophyllus [Thunb.] D. Don) seedlings to exponential fertilization

Abstract: Culturing slowly growing tree seedlings is a potential approach for managing the conflict between the increasing demand for ornamental stock and the decreasing area of farmlands due to urbanization. In this study, Buddhist pine (Podocarpus macrophyllus [Thunb.] D. Don) seedlings were raised in multishelves with light-emitting diode lighting in the spectrum of 17:75:8 (red:green:blue) at 190–320 μmol m-2 s-1 with controlled temperature and relative humidity at 19.5°C and 60%, respectively. Seedlings were fed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 40 publications
0
40
0
Order By: Relevance
“…Plant nutritional status refers to the synthesized symptom that is exposed under drivers of biomass accumulation and nutrient assimilation ( Xu et al, 2019;Wei et al, 2020b). Several studies have fully demonstrated that the variation in lighting spectra can shape plant nutritional statuses by modifying nutrient uptake, allocation, and utilization (Li et al, 2017;Li et al, 2018;Wang et al, 2020;Wei et al, 2020a;Wei et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…Plant nutritional status refers to the synthesized symptom that is exposed under drivers of biomass accumulation and nutrient assimilation ( Xu et al, 2019;Wei et al, 2020b). Several studies have fully demonstrated that the variation in lighting spectra can shape plant nutritional statuses by modifying nutrient uptake, allocation, and utilization (Li et al, 2017;Li et al, 2018;Wang et al, 2020;Wei et al, 2020a;Wei et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…The front layer of leaves was opened as a histogram. The leaf green index (GI) can be directly read from the background data of the histogram [42][43][44]. Leaf area can be calculated as the total pixels of the histogram divided by the square of the dpi [43][44][45].…”
Section: Sampling and Measurementmentioning
confidence: 99%
“…Exponential nutrient loading mostly synchronizes the pace of biomass accumulation in tree seedlings for most species (Duan et al, 2013;Wang et al, 2016). Exponential fertilization (EF) has been well documented to promote seedling quality through enhancing nutrient uptake to a level higher than needed for growth demand (Hawkins et al, 2005;Xu et al, 2019). The goal of harvesting nutrient-enriched seedlings promotes the interest to feed seedlings with EF at an applicative rate as high as possible.…”
Section: Introductionmentioning
confidence: 99%